2022
DOI: 10.1002/jcla.24194
|View full text |Cite
|
Sign up to set email alerts
|

A panel of three serum microRNA can be used as potential diagnostic biomarkers for nasopharyngeal carcinoma

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Many studies considered circulating miRNA could serve as a biomarker of ESCC and most of them reported an AUC around 0.7, 30 similar to our results. In addition, numerous studies have demonstrated that the combination of multiple miRNAs can achieve higher diagnostic efficacy than single miRNAs in tumor patients 31–34 . Therefore, we combined four plasma EVs‐derived miRNA for the diagnosis of ESCC, and the combination model showed optimum diagnostic capabilities for the detection of ESCC (AUC = 0.834), which was higher than that of total plasma miRNA panels (Figure 5D and Table S9).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Many studies considered circulating miRNA could serve as a biomarker of ESCC and most of them reported an AUC around 0.7, 30 similar to our results. In addition, numerous studies have demonstrated that the combination of multiple miRNAs can achieve higher diagnostic efficacy than single miRNAs in tumor patients 31–34 . Therefore, we combined four plasma EVs‐derived miRNA for the diagnosis of ESCC, and the combination model showed optimum diagnostic capabilities for the detection of ESCC (AUC = 0.834), which was higher than that of total plasma miRNA panels (Figure 5D and Table S9).…”
Section: Resultsmentioning
confidence: 92%
“…In addition, numerous studies have demonstrated that the combination of multiple miRNAs can achieve higher diagnostic efficacy than single miRNAs in tumor patients. 31 , 32 , 33 , 34 Therefore, we combined four plasma EVs‐derived miRNA for the diagnosis of ESCC, and the combination model showed optimum diagnostic capabilities for the detection of ESCC (AUC = 0.834), which was higher than that of total plasma miRNA panels (Figure 5D and Table S9 ). Thus, combining plasma EV‐derived miR‐636, miR‐7641, miR‐1246, and miR‐28‐3p model had better diagnostic efficiency for ESCC.…”
Section: Resultsmentioning
confidence: 97%
“…An extensive number of studies have demonstrated that miRNAs are involved in various biological processes, including tumor angiogenesis and vascular-related disorders ( Pourrajab et al, 2015 ; Mashreghi, 2017 ). In addition, some miRNAs have been reported as biomarkers of specific diseases ( Mariam et al, 2022 ), especially in tumors ( Li et al, 2022 ; Tu et al, 2022 ). Nonetheless, there are fewer studies focused on the comprehensive miRNA-gene interaction in IH.…”
Section: Introductionmentioning
confidence: 99%